Acquiring Three-Dimensional Deformation of Kilauea's South Flank From GPS and DInSAR Integration Based on the Ant Colony Optimization - Shi, Guo-qiang; He, Xiu-feng; Xiao, Ru-ya (IEEE geoscience and remote sensing letters, 2015)
To acquire a 3-D deformation of Kilauea's south flank, measurements from GPS and differential interferometric synthetic aperture radar (DInSAR) were integrated based on ant colony optimization. Constraints from GPS and DInSAR measurements were used to establish an energy function based on the Gibbs equation. In this letter, projection vectors used in the energy function were refined depending on the elevation and location of each ground pixel. To achieve stable and fast convergence of the algorithm, the proposed method was tested with different parameters. An ant colony size of 80 with 20 generation loops was designed to derive the 3-D deformation by solving the energy function. Both the ascending and descending interferometric pairs, as well as the GPS observations, of Kilauea volcano, Hawaii, were used in this letter. The results show good consistency with the GPS checkpoints. Root mean squares of 1.40, 1.88, and 2.2 cm were achieved in the directions of north-south, east-west, and zenith, respectively. The derived 3-D deformation maps will allow a better understanding of the source geometry associated with volcanic and seismic activities that result in surface deformation.